Behaviour of Dinosaurian Track-Makers in the Winton Formation (Cretaceous, Albian–Cenomanian) at Lark Quarry, Western Queensland, Australia: Running or Swimming?. Issue 1 (2nd January 2017) - Thulborn, Tony
ABSTRACT: A remarkable assemblage of dinosaur trackways in the Winton Formation (Albian–Cenomanian) at Lark Quarry, in western Queensland, Australia, has long been regarded as evidence of a stampede involving small theropods, whose tracks were classified in the ichnogenus Skartopus, and small ornithopods, whose tracks represented a second ichnogenus, Wintonopus . However, one recently-published study has claimed that existing interpretation of Lark Quarry is incorrect: it maintains that all the track-makers were ornithopods, that the ichnogenus Skartopus is a variant form of Wintonopus, and that most of the Lark Quarry track-makers were not running but more probably swimming downstream in a current of water. Those iconoclastic claims are investigated here and shown to be untenable. They derive from overgeneralized interpretation of the Lark Quarry track assemblage and invoke ad hoc auxiliary hypotheses which are either untestable or demonstrably incorrect. Closer inspection of the evidence underpinning those claims corroborates the existing interpretation of Lark Quarry as the site of a dinosaurian stampede and confirms the validity of the original distinction between theropod tracks ( Skartopus ) and ornithopod tracks ( Wintonopus ).